Prevalence and risk factors for urinary incontinence in healthy pregnant Brazilian women - Martins, Gisele; Soler, Zaida A. S. G.; Cordeiro, Jose Antnio; Amaro, João Luiz [UNESP]; Moore, Katherine N. (Springer London Ltd, 2010)
Physiological and anatomical changes of pregnancy are risk factors for lower urinary tract symptoms (LUTS). This study aimed to evaluate the prevalence and risk factors for urinary incontinence (UI) in healthy pregnant women.A cross-sectional study was conducted in pregnant Brazilian women who enrolled in the primary health-care system in Sao Jose do Rio Preto, Brazil. Face-to-face interview and completion of two-part questionnaire were administered and done which evaluated the presence of LUTS pre- and during pregnancy. The data were analyzed by logistic regression.Five hundred pregnant women were enrolled ranging from first to third trimester. LUTS present in 63.8% in these women; the main associated risk factors were multiparity and prepregnancy LUTS as well as smoking, constipation, and daily coffee intake.The prevalence of UI during pregnancy is high, highlighting the presence of the risk factors associated with UI during pregnancy.
Keywords: Epidemiology; Pregnancy; Primary prevention; Urinary incontinence